EVALUATION OF DIFFERENT REARING MEDIA FOR CORCYRA CEPHALONICA (STAINTON) UNDER LABORATORY CONDITION - S. K. MEHENDALE; M.B. PATEL; C. U. SHINDE (The Bioscan, 2014)
The rearing media to improve the mass production of C. cephalonica as a factitious host revealed three promising media viz., T3 (sorghum + groundnut + powdered yeast), T4 (sorghum + gram + powdered yeast) and T6 (sorghum + cowpea + powdered yeast) with heavier larvae in T3 (53.33 mg), T4 (52.50 mg) and T6 (54.50 mg). The heavier pupae were also recorded in T4 (34.67 mg), T6 (34.17 mg) and T3 (33.17 mg) while heavier female moths were recorded in T3 (39.33 mg), T4 (34.83 mg) and T6 (34.0 mg). The maximum moth emergence were in T3 (523.84), T4 (476.34) and T6 (470.0). Whereas, the maximum total females were noticed in T3 (266.17), T6 (251.50) and T4 (243.34). The maximum fecundity was recorded in Corcyra females emerged from T3 (611.54), T4 (494.28) and T6 (481.08). Moreover, the maximum projected egg laying was realized from the females emerged from T3 (8.14 cc), T6 (6.10 cc) and T4 (6.01 cc). The significantly maximum weight of 100 Corcyra egg was exhibited with females emerged from T4 (3.73 mg), T6 (3.70 mg). The maximum length and breadth of egg was obtained from females emerged from T4 (0.70 and 0.40 mm), T6 (0.62 and 0.39 mm) and T3 (0.56 and 0.35 mm), respectively. However, no much detrimental impact on the life cycle of C. cephalonica were exhibited through modification of rearing media though the female preponderance (sex ratio as M: F) was noticed in T3 (0.97:1), T4 (0.96:1) and T6 (0.87:1).